Fall of another myth for colon cancer: Duration of symptoms does not differ between right- or left-sided colon cancers - (:unkn) unknown (AVES, 2019)
Background/Aims: Patients with colorectal cancer continue to present with relatively advanced tumors that are associated with poor oncological outcomes. The aim of the present study was to assess the association between localization, symptom duration, and tumor stage. Materials and Methods: A prospective, multicenter cohort study was conducted on patients newly diagnosed with a histologically proven colorectal adenocarcinoma. Standardized questionnaire-interviews were performed. Data were collected on principal presenting symptoms, duration of symptoms (time to first presentation to a doctor and time to diagnosis) and treatment, diagnostic procedures, tumor site, and stage of the tumor (tumor, node, and metastasis (TNM)). Results: A total of 1795 patients with colorectal cancer were interviewed (mean age: 60.76 +/- 13.50 years, male patients: 1057, patients aged >50 years: 1444, colon/rectal cancer: 899/850, right side/left side: 383/1250, stage 0-1-2/stage 3-4: 746/923). No statistically significant correlations were found between duration of symptoms and either tumor site or stage. Principal presenting symptoms were significantly associated with left colon cancer. Patients who had anemia, change in bowel habits, anal pruritus or discharge, weight loss, and tumor in right colon had a significantly longer symptom time. Conclusion: Symptom duration is not associated with localization, nor is the tumor stage. Diagnosis of colorectal cancer at an earlier stage may be best achieved by screening of the population.
Keywords: Colorectal cancer; symptom duration; localization; COLORECTAL-CANCER; DELAYED DIAGNOSIS; THERAPEUTIC DELAY; SURVIVAL; STAGE; EMERGENCY; PROGNOSIS